Sistem Pakar Metode Case-Based Reasoning Untuk Deteksi Penyakit Stunting Pada Anak - Muhamad Brilliant; Nizamiyati Nizamiyati (Institut Informatika dan Bisnis Darmajaya, 2022)
Toddlers have a very high risk of being stunted such as chronic malnutrition, height, or body length that is too small for the same age group. During pregnancy Malnutrition can be experienced by infants, even in the early days of birth, but stunting cannot be experienced for babies under two years of age. One of the efforts to increase the level of health in children is by identifying stunting. Manual identification by measuring the child's height and weight is considered ineffective. The Focus of this research is creating an expert system for detecting stunting in children using the Case based reasoning (CBR) method using website-based technology so that it can be used anytime and anywhere.. This study uses the RnD (Research and Development) method with the stages in the ADDIE research as follows (1) Analysis (2) Design (3) Development, (4) Implementation (5) Evaluation. The results of the research are in the form of an expert system for detecting stunting in children using the Case-based reasoning (CBR) method which has succeeded in detecting/diagnosing stunting in children and can provide suggestions for several diagnostic results as well as solutions from the results of the diagnosis, the application is made website-based so that it can be used by anyone, anywhere, and anytime. From the results of application testing using the white box testing method, the scenario is appropriate and the application is running as it should.